Review of Electronic Medical Records in Indonesia and its Developments Based on Legal Regulations in Indonesia and its Harmonization with Electronic Health Records (Manual for Developing Countries) - Tirsa Sharon Tilaar; Pan Lindawaty Suherman Sewu (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
A medical record is a system that aims to track health and hospital visits. It can also be used to assist doctors and nurses in understanding medical history and to assist medical personnel in making decisions about treating patients. The method used in this research is the normative juridical research method. The specifics of this research is descriptive-analytical research, which is research that seeks to analyze legal issues and the legal system, in order to better understand them so that conclusions can be drawn. Medical records are part of the obligations of all doctors and dentists to carry out their medical practice. This is in accordance with "Article 46 of Law number 29 of 2004 concerning Medical Practice. As the executor of article 46 of law number 29 of 2004 concerning medical practice, the Minister of Health Regulation number 24 of 2022 concerning Medical Records was enacted as a substitute for the previous regulation, namely Regulation of the Minister of Health number 269/MENKES/PER/2008 concerning Medical Records”. This research provides an understanding of electronic medical record regulations and the development of the implementation of EMR (Electronic Medical Record). In the implementation of EMR (Electronic Medical Record) it is necessary to revamp the EMR (Electronic Medical Record) system as a whole so that an effective and efficient implementation of EMR (Electronic Medical Record) can be created.